Synthesis and Characterization of Cu-Doped SnO\(_2\) (Sn\(_{0.98}\)Cu\(_{0.02}\)O\(_2\)) Thin Film by Sol-gel Technique for LPG Sensing (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2020)
In this study Cu-doped SnO\(_2\) (Sn0.98Cu0.02O2) thin film was deposited on the glass substrate by sol-gel dip-coating technique. The structural, morphological, and optical properties of the prepared film were studied by X-ray diffraction (XRD), Optical Microscopy (OM), and Uv-visible spectroscopy respectively. XRD analysis revealed that the structure of our deposited film is hexagonal and the crystallite size is found to be 3.89 nm. The surface morphological studied by (OM) indicates that the film is homogeneous. The result of optical properties shows high transmittance estimated at 73.98% and the optical band gap was found 3.961 eV. The gas sensing properties of the prepared film were examined at different operating temperatures and different volume concentrations of liquefied petroleum gas (LPG). It was found that Cu doped SnO2 has an excellent response and recovery time for 1.8 vol% LPG at 250 \(^°\)C, their values are equal to 11s and 19s respectively, obtained sensors presents high selectivity to LPG against H\(_2\)S, NH\(_3\) and CO\(_2\).
Keywords: SnO\(_2\) thin film; LPG sensing; Sol-gel; Reducing gas; Response